Pleuroscopy or video-assisted thoracoscopic surgery for exudative pleural effusion: a comparative overview - Sajawal Ali, Muhammad; Light, Richard W.; Maldonado, Fabien (Journal of Thoracic Disease, 2019)
Exudative pleural effusions, such as malignant and tuberculous pleural effusions, are associated with notable morbidity and mortality. Unfortunately, a significant number of these effusions will remain undiagnosed despite thoracentesis. Traditionally, closed pleural biopsies have been the next best diagnostic step, but the diagnostic yield of blind closed pleural biopsies for malignant pleural effusions is insufficient. When image-guided targeted biopsies are not possible, both pleuroscopy and video-assisted thoracoscopic surgery are reasonable options for obtaining pleural biopsies, but the decision to select one procedure over the other continues to raise much debate. Pleuroscopy (aka. medical thoracoscopy, local anaesthetic thoracoscopy) is a relatively common procedure performed by interventional pulmonologists in the bronchoscopy suite with local anesthesia, often as an outpatient procedure, on spontaneously breathing patients. Video-assisted thoracoscopic surgery, on the other hand, is performed by thoracic surgeons in the operating room, on mechanically ventilated patients under general anesthesia, though admittedly considerable overlap exists in practice. Both pleuroscopy and video-assisted thoracoscopic surgery have reported diagnostic yields of over 90%, although pleuroscopy more often leads to the unsatisfactory diagnosis of ‘non-specific’ pleuritis. These cases of ‘non-specific’ pleuritis need to be followed up for at least one year, as 10–15% of them will eventually lead to the diagnosis of cancer, typically malignant pleural mesothelioma. Both procedures have their pros and cons, and it is therefore of paramount importance that all cases be discussed as part of a multidisciplinary approach to diagnosis within a “pleural team” that should ideally include interventional pulmonologists and thoracic surgeons.